Feedback-controlled adiabatic quantum computation - Richard D. Wilson; Alexandre Zagoskin; Sergey Saveliev; Mark Everitt; Franco Nori (2012)
We propose a simple feedback-control scheme for adiabatic quantum computation with superconducting flux qubits. The proposed method makes use of existing on-chip hardware to monitor the ground-state curvature, which is then used to control the computation speed to maximize the success probability. We show that this scheme can provide a polynomial speed-up in performance and that it is possible to choose a suitable set of feedback-control parameters for an arbitrary problem Hamiltonian.